Religious tolerance in Malaysia: problems and challenges - Nur Farhana Abdul Rahman; Khadijah Mohd Khambali @ Hambali (Universiti Kebangsaan Malaysia, 2013)
Every religion is normally perceived from their own religion to tend toward exclusiveness by claiming that their religion is the only true religion, offering the true revelation and the true way of salvation. This exclusiveness started with desire to know the religious status or truth position among other religions. The question on which religion is the ideal religion and ultimately the truest one has always been raised and debated among people of religions. This polemic can be a seed of many conflicts and disagreements between religions in many parts of the world,including Malaysia as a multi-religious country. This is a preliminary study which attempts to explore issues and challenges pertaining to religious tolerance as practiced in Malaysia. This research is a qualitative research which data are gathered from various sources including books, journals, magazines, newspapers,articles and internet sources related to the topic as well as in depth interview with qualified persons. The data will then be analysed using document analysis method. The result shows that religious tolerance in this country is seen working under various and distinctive understanding. The main challenges to practising religious tolerance in Malaysia emerged from none guidance module to practising religious tolerance especially which stated the limitation and the rule in religious tolerance applicable in Malaysia context and lack of understanding of religious tolerance needed within adherents of religion which cause prejudices against the adherents of religions.